Impact of cardiac surgical timing on the neurodevelopmental outcomes of newborns with Complex congenital heart disease (CHD) - Lenoir, Marien; Beretti, Thibault; Testud, Benoit; Resseguier, Noémie; Gauthier, Kim; Fouilloux, Virginie; Gran, Célia; Paoli, Florent; El-Louali, Fedoua; Aldebert, Philippe; Blanc, Julie; Soulatges, Camille; et al. (Frontiers in Pediatrics, 2023)
Background More than half of infants with complex congenital heart disease (CHD) will have a neurodevelopmental disorder of multifactorial causes. The preoperative period represents a time-window during which neonates with complex CHD are in a state of hypoxia and hemodynamic instability, which fosters the emergence of brain injuries and, thus, affects early brain networks and neurodevelopmental outcomes. Currently, there is no consensus regarding the optimal age for cardiac surgery in terms of neurodevelopmental outcomes, and its definition is a real challenge. Our aim is to determine the relationship between cardiac surgical timing and long-term neurodevelopmental outcomes for various types of complex CHD. Methods We hypothesize that earlier surgical timing could represent a neuroprotective strategy that reduces perioperative white matter injuries (WMIs) and postoperative morbidity, leading to improved neurodevelopmental outcomes in infants with complex CHD. Firstly, our prospective study will allow us to determine the correlation between age at the time of surgery (days of life) and neurodevelopmental outcomes at 24 months. We will then analyze the correlation between age at surgery and (i) the incidence of WMIs (through pre- and postoperative MRIs), (ii) postoperative morbidity, and (iii) the duration of the hospital stay. Implications and Dissemination This research protocol was registered in the Clinical Trial Registry (National Clinical Trial: NCT04733378). This project aims to help launch the first Neurocardiac Investigation Clinic in Marseille — AP-HM — to propose an overall personalized monitoring and treatment program for patients operated on for complex CHD.